Evaluation of Education Program for Employee Competency Enhancement - Sigit Triyono; Yetti Supriyati; Billy Tunas (European Scientific Journal, ESJ, 2019)
The Indonesian Bible Society has the task of translating the Bible and its parts from original manuscripts into Indonesian and other regional languages spread throughout Indonesia. In the globalization era, it is important to improve the skill of human resources in order to keep the institution running well. This paper focuses on describing how to evaluate an Education Program for employee competency enhancement. The Education Program is a part of human resources development program of which its evaluation is important to see the effectiveness of the implementation of the program in the Indonesian Bible Society. This research uses Stake’s Countenance Evaluation Model, and it focuses on implementation concerning input, process, and outcome. Subjects of the research are employees including structural management. Data collected were analyzed using descriptive method with qualitative approach. Research findings show that managing the human resources could be supported using skill and competency. Curriculum development is important to be revised regularly. In addition, improving employee’s skill and competency can motivate them to do their job well.